Answer:
-6
Explanation:
Lets assume a number be "x".
As given, lets put in an expression:
=
--- (first)
=
----- (second)
As known both the expression are same.
⇒
=
![5x+10](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8pm189x479jmne3h041kreqrsigh9xds4e.png)
Opening the parenthesis and distributing the number 4 with 2x and 7.
⇒
![8x+28= 5x+10](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8xgje21pphn1pz5717t5xt4ckut2utfhgf.png)
subtracting both side by 28 and 5x
⇒
![3x= -18](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qtt4g1990t0cvdn3cte4dzu4suyibp3q14.png)
cross multiplying
∴ x=
![(-18)/(3) = -6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/u1eazzrd7qnnl21j2uxuk9nqij0ve0q0l2.png)
x= -6
On subtituting the value of x on the expression.
=
![5x+10](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8pm189x479jmne3h041kreqrsigh9xds4e.png)
We get, -20=-20, which is equal.